VARIASI KOMPOSISI PAKAN BUATAN UNTUK SERANGGA: SUATU KAJIAN PUSTAKA - SUSRAMA, I GEDE KETUT (Jurnal Biologi Udayana, 2018)
Artificial diet for insect rearing is necessary at the time a lot of insects required periodically and continuously such as for pesticide efficacy research, biodiversity conservation, and for the activity of fruit fly management with the sterile male technique for instance where it needs millions fruit flies weekly to be sterilized and then subsequently released. Insect artificial diet will also increase the efficiency of time, energy and fund in the procurement of insects compared to insect rearing with its natural diet. Various artificial diet classifications and its compositions have been developed so far in varying degrees of rearing success.